SignaLink3: a multi-layered resource to uncover tissue-specific signaling networks - Csabai, Luca; Fazekas, Dávid; Kadlecsik, Tamás; Szalay-Bekő, Máté; Bohár, Balázs; Madgwick, Matthew; Módos, Dezső; Ölbei, Márton; Gul, Lejla; Sudhakar, Padhmanand; Kubisch, János; Oyeyemi, Oyebode James; et al. (Nucleic acids research, 2022)
Signaling networks represent the molecular mechanisms controlling a cell's response to various internal or external stimuli. Most currently available signaling databases contain only a part of the complex network of intertwining pathways, leaving out key interactions or processes. Hence, we have developed SignaLink3 (http://signalink.org/), a value-added knowledge-base that provides manually curated data on signaling pathways and integrated data from several types of databases (interaction, regulation, localisation, disease, etc.) for humans, and three major animal model organisms. SignaLink3 contains over 400 000 newly added human protein-protein interactions resulting in a total of 700 000 interactions for Homo sapiens, making it one of the largest integrated signaling network resources. Next to H. sapiens, SignaLink3 is the only current signaling network resource to provide regulatory information for the model species Caenorhabditis elegans and Danio rerio, and the largest resource for Drosophila melanogaster. Compared to previous versions, we have integrated gene expression data as well as subcellular localization of the interactors, therefore uniquely allowing tissue-, or compartment-specific pathway interaction analysis to create more accurate models. Data is freely available for download in widely used formats, including CSV, PSI-MI TAB or SQL.
Online verfügbar 11 October 2021
Gesehen am 27.09.2022